THE EFFECT OF NUTRITION EDUCATION WITH THE EMOTIONAL DEMONSTRATION METHOD ON MOTHER's AWARENESS IN FEEDING UNDERWEIGHT TODDLERS - baiq dewi Sukma; Nurmaningsih Nurmaningsih; Solatia Hairun Nisa (Jambura Journal of Health Sciences and Research, 2021)
The fundamental health research 2018 stated that the incidence of malnutrition in Indonesia is 17.7% and West Nusa Tenggara is the second largest malnutrition in Indonesia, which is 29.5%, with the highest incidence of malnutrition in West Lombok Regency at 30%. The nutritional condition of toddlers is influenced by family care, especially mothers in terms of feeding. The awareness of nutrition has a positive relationship with behavior where mothers who have less awareness have less opportunities to behave less. This has an effect on the provision of unhealthy food, which causes malnutrition in children under five. Based on these facts, education about the importance of adequate nutrition for toddlers are very important to solve this problem. This study aims to analyze the effect of nutritional education with the emotional demonstration method on maternal behavior in feeding to underweight toddlers. This type of research is the Open-Label Non Randomized Controlled Trial Design with a Pre-Post with Control Design research design. The sample in this study amounted to 54 underweight toddlers mothers with 27 people as the treatment group and 27 people as the control group. The research location was conducted in Beleke Village, West Lombok Regency. The result is an increase in maternal behavior towards the feeding pattern of underweight toddlers. Keywords: Underweight Toddlers, Behavior, Emotional-Demonstration